Gout, Hyperuricaemia and Crystal-Associated Disease Network (G-CAN) consensus statement regarding labels and definitions of disease states of gout. Issue 11 (9th September 2019) - Bursill, David; Taylor, William J; Terkeltaub, Robert; Abhishek, Abhishek; So, Alexander K; Vargas-Santos, Ana Beatriz; Gaffo, Angelo Lino; Rosenthal, Ann; Tausche, Anne-Kathrin; Reginato, Anthony; Manger, Bernhard; Sciré, Carlo; et al.
Abstract : Objective: There is a lack of standardisation in the terminology used to describe gout. The aim of this project was to develop a consensus statement describing the recommended nomenclature for disease states of gout. Methods: A content analysis of gout-related articles from rheumatology and general internal medicine journals published over a 5-year period identified potential disease states and the labels commonly assigned to them. Based on these findings, experts in gout were invited to participate in a Delphi exercise and face-to-face consensus meeting to reach agreement on disease state labels and definitions. Results: The content analysis identified 13 unique disease states and a total of 63 unique labels. The Delphi exercise (n=76 respondents) and face-to-face meeting (n=35 attendees) established consensus agreement for eight disease state labels and definitions. The agreed labels were as follows: 'asymptomatic hyperuricaemia', 'asymptomatic monosodium urate crystal deposition', 'asymptomatic hyperuricaemia with monosodium urate crystal deposition', 'gout', 'tophaceous gout', 'erosive gout', 'first gout flare' and 'recurrent gout flares'. There was consensus agreement that the label 'gout' should be restricted to current or prior clinically evident disease caused by monosodium urate crystal deposition (gout flare, chronic gouty arthritis or subcutaneous tophus). Conclusion: Consensus agreement has been established for the labels and definitions of eight gout disease states, including 'gout' itself. The Gout, Hyperuricaemia and Crystal-Associated Disease Network recommends the use of these labels when describing disease states of gout in research and clinical practice.